2015
DOI: 10.1007/s00223-015-9966-8
|View full text |Cite
|
Sign up to set email alerts
|

Deteriorating Effect on Bone Metabolism and Microstructure by Passive Cigarette Smoking Through Dual Actions on Osteoblast and Osteoclast

Abstract: There is no clear evidence to show the direct causal relationship between passive cigarette smoking and osteoporosis. Furthermore, the underlying mechanism is unknown. The objective of this study is to demonstrate the effects of long-term passive cigarette smoking on bone metabolism and microstructure by a mouse model and cell culture systems. BALB/c mice were exposed to 2 or 4 % cigarette smoke for 14 weeks. The bone turnover biochemical markers in urine and serum and also the bone micro-architecture by micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…First, tobacco smoke exposure can indirectly alter bone function by increasing parathyroid hormone release, increasing cortisol production or reducing vitamin D metabolism (Abate, Vanni, Pantalone, & Salini, 2013;Yoon et al, 2012). Second, tobacco smoke can directly act on bone by targeting the proliferation, differentiation and matrix deposition of bone-forming cells called osteoblasts (Ko et al, 2015). In either case, disturbance in the normal pattern of bone remodeling can contribute to the development of osteoporosis.…”
mentioning
confidence: 99%
“…First, tobacco smoke exposure can indirectly alter bone function by increasing parathyroid hormone release, increasing cortisol production or reducing vitamin D metabolism (Abate, Vanni, Pantalone, & Salini, 2013;Yoon et al, 2012). Second, tobacco smoke can directly act on bone by targeting the proliferation, differentiation and matrix deposition of bone-forming cells called osteoblasts (Ko et al, 2015). In either case, disturbance in the normal pattern of bone remodeling can contribute to the development of osteoporosis.…”
mentioning
confidence: 99%
“…In our study, there was a prevalence of cylindrical bone structural elements in the CSO group, that was increasing from 21 st to 128 th days, representing an increase of 51,1% in relation to the control. Ko et al (2015), in their study, showed a similar result indicating that the secondhand smoke exposure increased in 46% the value of the SMI in relation to the control, confirming the osteopenic condition [1]. Sasaki M et al (2018) showed in rats, that the secondhand smoke exposure, from gestation and birth to 28th day of life, increased the bone volume and induced to the osteoporosis, thanks to the spatial orientation of the tissue microstructure [38].…”
Section: Discussionmentioning
confidence: 59%
“…There is an estimated that 40% of the children in the world, 33% of boys and 35% of girls, are exposed to the secondhand smoke. [1]. The cigarette smoke inhaled in a passive way consists of 15% of the mainstream smoke, the smoke inhaled by the current smoker and 85% of the sidestream smoke.…”
Section: Introductionmentioning
confidence: 99%
“…Although periostin effect on cell properties has already been described in several cell lines [ 30 33 ] we wanted to asses periostin effects in two murine cell lines directly implicated in bone—physiology and with antagonistic functions; the pre-osteoblastic MC3T3-E1 cell line, a good model for studying in vitro osteoblast differentiation; and the murine macrophage RAW264.7 cell line, with the capacity to differentiate to osteoclast-like cells. Both cell lines have been extensively used in order to unravel mechanisms towards osteoblastic and osteoclastic differentiation as well as to assay the effects of chemicals on bone physiology [ 34 42 ]. For that purpose, a vector containing periostin cDNA was used to transfect both cell lines and the presence of a immunoreative band at the expected size (90 kDa) was confirmed by western-blot analysis using an anti-periostin antibody ( Fig 1a , top).…”
Section: Resultsmentioning
confidence: 99%